Therapeutic effectiveness of Glyceryl Trinitrate (GTN) in the Treatment of uncomplicated Chronic Anal Fissure (CAF) - Khatun, Shima Akter; Islam, Md Rashidul; Khatun, Halima; Islam, Farhana; Saha, Shusmita (Journal of Dhaka National Medical College & Hospital, 2021)
Objective: To determine the therapeutic effectiveness of Glyceryl trinitrate (GTN) in the treatment of uncomplicated chronic anal fissure Materials and Methods: Prospective observational Study conducted in a private hospital in Dhaka City from Jan 2019 to Dec 2019. Forty eight patients of chronic anal fissure were included in this study. There were 28 (58.33%) females and 20 (41.66%) males with mean age of 37.Pain was documented using visual analogue scale. At presentation all patients (100%) perceived pain as severe pain on Visual Analogue Scale. Patients were started treatment with local application of Glyceryl Trinitrate (GTN) gel, twice daily and reassessed after 04 weeks and 08 weeks of treatment respectively. Pain and healing of fissure were documented. Results: Significant pain relief was observed in 46% patient & fissure healing was observed in 31.25% patient. The commonest side effect of treatment was headache (26%). Conclusion: Glyceryl trinitrate is very effective in the treatment of chronic anal fissure and is the drug of choice in conservative treatment of anal fissures and in patients with contraindications for surgery J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 26-29